Shia is One Of the Sects in Islam - Novita Dewi, Resti; Maulana, Deni; Oznur Tasdoken (Al-Mubin, 2024)
Islam as a religion has many branches of teachings, one of which is Shia. Shia is a sect of Islam based on the views of Sayyidina Ali (the fourth caliph) and his descendants. This sect emerged at the beginning of Khulafaurrasyidin’s leadership and has loyal followers. They believe Sayyidina Ali should become the successor caliph to the Prophet Muhammad SAW based on the Prophet’s will. Shia has developed into various sects and has become an issue that requires exceptional understanding and attention in Islamic studies. Debates and polemics often arise around Shiism, so it is essential to understand its various types and doctrines. This literature research discusses four Shiite sects: Shiite Itsna Asyariah, Shiiah Sab’iah, Shiiah Zaidiah, and Shiiah Ghulat. Shia Itsna ‘Asyariyah is a sect that recognizes twelve imams as Islamic community leaders and has the most prominent followers. Shiite Sab’iah recognizes seven imams. The Zaidiyah Shiites, whose name is Zaid bin Ali Zainal Abidin, have a moderate attitude in dealing with the issue of Ali bin Abi Talib’s leadership and in assessing the three previous caliphs. Meanwhile, the Ghulat Shiites tend to be extreme in supporting Ali. Abu Zahrah explained that the Ghulat Shiites are a group that places Ali in a position like God; some even have a higher concept than the Prophet Muhammad. This research aims to provide a broader understanding of various Shia sects. Understanding these schools provides many perspectives on how religious thought is formed, which needs to be considered